HUBUNGAN KEPATUHAN DIET DENGAN KEJADIAN KOMPLIKASI PADA PENDERITA DIABETES MELLITUS TIPE 2 DI PUSKESMAS GONDOKUSUMAN I YOGYAKARTA - Novia Handayani; Ani Mashunatul Mahmudah (Surya Medika: Jurnal Ilmiah Ilmu Keperawatan dan Ilmu Kesehatan Masyarakat, 2017)
Background: Adhering to a series of diets in people with type 2 diabetes is a big challenge to avoid complications. Diabetes mellitus is a long-term disease, so if neglected complication of diabetes mellitus disease can attack all the body part resulting from uncontrolled blood sugar level in people with diabetes. Objective: To know the relationship of diet compliance with the incidence of complications in patients with type 2 diabetes in Puskesmas Gondokusuman I Yogyakarta. Method: This research type is quantitative with Cross Sectional approach. Respondents in this study were 50 patients with type 2 diabetes and were taken with purposive sampling technique. Data analysis using Chi Square. Results: There was a significant relationship between dietary adherence and the incidence of complications in type 2 diabetes mellitus. This means that patients who adhere to the diet are likely to have very small complications. With result (p) α that is 0,011 0,05. Conclusion: The incidence of complications is strongly influenced by dietary adherence. Therefore it is necessary to increase the extension by health personnel about the importance of adhere to diet in patients with disbetes melitus properly so that no complications arise.